Slanted Ag-Al alloy nanorods arrays for highly active and stable surface-enhanced Raman scattering substrates. (21st March 2019) - Liu, Yuehua; Ma, Lingwei; Zou, Sumeng; Zhao, Fengtong; Wang, Yanfeng; Ling, Yunhan; Zhang, Zhengjun
Abstract: Aluminum has been established as an earth-abundant and low-cost alternative to gold and silver for plasmonic applications. Particularly, aluminum largely tends to combines with oxygen compared with silver. Here, a simple glancing angle deposition technique is presented to prepare Ag-Al alloy nanorods (NRs) with a small amount of aluminum. The effect of aluminum is to combine oxygen or corroded substances under certain conditions, such as in the air and in etchants. Beside this, owing to the large diffusion coefficient of aluminum in a Si wafer, the aluminum diffuses easily into a Si wafer, so the bonding force between the Ag-Al alloy NRs and Si wafer can be improved accordingly. In this work, 3.5 at% Al alloy NRs are optimal to exhibit high surface-enhanced Raman scattering (SERS) sensitivity, long-time stability as well as strong bonding force with a Si wafer. Ag-Al alloy NRs make a metal-metal alloy a promising material platform to develop pretty sensitive as well as stable SERS substrates.